Morphotropic phase-boundary-like characteristic in a lead-free and non-ferroelectric (1-x) NaNb O3 -xCaTi O3 system - Tripathi S.; Pandey D.; Mishra S.K.; Krishna P.S.R. (My University, 2025)
We report here an anomalous peak in the composition dependence of the dielectric permittivity of non-ferroelectric (1-x) NaNb O3 -xCaTi O3 ceramics for the composition range 0.10<x<0.20. This is reminiscent of a similar phenomenon in the ferroelectric morphotropic phase boundary ceramics. Rietveld analysis of the powder x-ray diffraction data for various compositions reveals that this peak is linked with a change of crystal structure from one orthorhombic phase in the Pbma space group for 0≤x≤0.10 to another orthorhombic phase in the Pbnm space group for x≥0.20 through an intermediate long period modulated orthorhombic phase whose lattice parameter is ∼14 times the lattice parameter of the Pbnm phase of CaTi O3 in the [010] direction (q∼ [0,1/14,0]). © 2008 The American Physical Society.